Estado, educação e racismo : uma abordagem dialética da Lei federal nº 10.639/03 como política pública de enfrentamento do racismo na escola - Mendes, Samuel da Silva (2018)
This research paper is inserted in the field of study about educational public policies, with an approach on the racial-ethnic relations and has as title “State, Education and Racism: a dialectical approach of the Federal Law n° 10.639/03 as public policy of confront of the racism in the school”. In this study, we proposed to reflect upon the following question: What has been the response of the Brazilian state in terms of public policies of education towards the current diagnosis of the racism that arises in the school routine? Such questioning takes in consideration the fact that the implementation of the public policies for the racial-ethnic relations in the school has not been an easy task, bearing in mind that more than a decade of the endorsement of the Law 10.639/03 has passed and very little has changed with regard to the situation of the Afro-Brazilian student in the school environment. With this is mind, we aimed at analyzing how the model of State and the ideology that sustains certain government interfere in the paths of the public policies in education and what is their impact on the situation that looms over the Afro-Brazilians. We sought, therefore, on a time frame that spans the period of a bit more than a decade in which the Workers’ Party (PT), in the administrations of Luiz Inácio Lula da Silva and Dilma Rousseff, was ahead of the federal government, to comprehend the paths that lead to the formulation of educational public policies which contemplated the yearnings of the Afro-Brazilian population, as well as to reflect upon the courses of these policies in the present time. For this purpose, in this study, we catalogued the following objective: reflect upon the relation between the State, the education and the racial-ethnic questions, as well as upon the treatment given to racism in the field of the educational public policies. The racial conflicts present in the school are still treated, in most cases, as isolated and individualized phenomena and not as results of a society in which racism intermediates the family, working and schooling relations. Transforming the racial situation of prejudice in the Brazilian education demands much work, political fight and dedicated studies for the comprehension of the phenomenon. In this investigation, we analyzed the Law nº 10.639/03 and some documents that emerge from it as instruments of questioning of the established order, insofar as these put in check the ideological constructions of domination and are presented as tools of resistance for better conditions of existence of the Afro-Brazilian population. A careful reflection of the theme reinforces the importance of thinking about the educational public policies as tools of combat of the school racism, as well as overcoming the condition of inferiority in which the Afro-Brazilian is positioned when analyzed the place occupied by the population in the social pyramid. An anti-racist education emerges as a path to the resilience of this reality not just in the school, but also in society in general, since only a critical education of the status quo and of the racial and social inequalities can lead to transformation of the stark reality of the historically excluded populations.